Application of the virtual crack closure technique (VCCT) using tetrahedral finite elements to calculate the stress intensity factor. (August 2021) - Liu, Yan-Ping; Li, Tian-Jun
Highlights: Modified VCCT was proposed for calculating SIF using tetrahedral finite elements. Formulations of the modified VCCT were proposed for arbitrary triangular areas. Arbitrary tetrahedral finite element can be employed to calculate SIF. Structures with cracks can be meshed automatically using tetrahedral elements. Abstract: This paper proposes an approach for calculating the stress intensity factor (SIF) based on the virtual crack closure technique (VCCT) using tetrahedral finite elements. An important feature of this approach is that tetrahedral element meshes with no strict requirements of shape can be employed to calculate the SIF with the VCCT. Therefore, structures with cracks can be meshed automatically and easily using arbitrary tetrahedral elements. Two cases with different crack shapes are presented to assess the validity of the proposed approach. Reasonable agreement between the proposed method and analytical solutions are obtained.